Public administration and democracy : the complementarity principle - Bertelli, Anthony Michael; Schwartz, Lindsey J. (Cambridge elements. Elements in public and nonprofit administration, 2022)
This Element argues for a complementarity principle - governance values should complement political values - as a guide for designing the structures and procedures of public administration. It argues that the value-congruity inherent in the complementarity principle is indispensable to administrative responsibility. It identifies several core democratic values and critically assesses systems of collaborative governance, representative bureaucracy, and participatory policymaking in light of those values. It shows that the complementarity principle, applied to these different designs, facilitates administrative responsibility by making the structures themselves more consistent with democratic principles without compromising their aims. This title is also available as Open Access on Cambridge Core.